Clinical Epidemiology of Extubation Failure in the Pediatric Cardiac ICU: A Report From the Pediatric Cardiac Critical Care Consortium*. Issue 9 (November 2015) - Gaies, Michael; Tabbutt, Sarah; Schwartz, Steven M.; Bird, Geoffrey L.; Alten, Jeffrey A.; Shekerdemian, Lara S.; Klugman, Darren; Thiagarajan, Ravi R.; Gaynor, J. William; Jacobs, Jeffrey P.; Nicolson, Susan C.; Donohue, Janet E.; et al.
Abstract : Objective: To describe the clinical epidemiology of extubation failure in a multicenter cohort of patients treated in pediatric cardiac ICUs. Design: Retrospective cohort study using prospectively collected clinical registry data. Setting: Pediatric Cardiac Critical Care Consortium registry. Patients: All patients admitted to the CICU at Pediatric Cardiac Critical Care Consortium hospitals. Interventions: None. Measurements and Main Results: Analysis of all mechanical ventilation episodes in the registry from October 1, 2013, to July 31, 2014. The primary outcome of extubation failure was reintubation less than 48 hours after planned extubation. Repeated-measures analysis using generalized estimating equations to account for within patient and center correlation was performed to identify risk factors for extubation failure. Adjusted extubation failure rates for each hospital were calculated using logistic regression controlling for patient factors. Of 1, 734 mechanical ventilation episodes (1, 478 patients at eight hospitals) ending in a planned extubation, there were 100 extubation failures (5.8%). In multivariable analysis, only longer duration of mechanical ventilation was significantly associated with extubation failure ( p = 0.01); the failure rate was 4% when ventilated less than 24 hours, 9% after 24 hours, and 13% after 7 days. For 503 patients intubated and extubated in the cardiac operating room, 15 patients (3%) failed extubation within 48 hours (12 within 24 hr). Case-mix-adjusted extubation failure rates ranged from 1.1% to 9.8% across hospitals. Patients failing extubation had greater median cardiac ICU length of stay (15 vs 3 d; p < 0.001) and in-hospital mortality (7.9 vs 1.2%; p < 0.001). Conclusions: Though extubation failure is uncommon overall, there may be opportunities to improve extubation readiness assessment in patients ventilated more than 24 hours. These data suggest that extubation in the operating room after cardiac surgery can be done with a low failure rate. We observed variation in extubation failure rates across hospitals, and future investigation must elucidate the optimal strategies of high-performing centers to reduce ventilation time while limiting extubation failures. Abstract : Supplemental Digital Content is available in the text.